Comparación de suero autólogo con un producto comercial como complemento en el tratamiento de úlceras corneales no complicadas en caninos (2012)
ABSTRACT: Corneal ulcers are among the most common presentations of ocular ailments in dogs. Objective: this study compares the efficacy of a commercial ointment based on vitamin A, E and hydrolyzed casein, with the use of autologous serum eyedrops in the re-epithealization of uncomplicated corneal ulcers. Methods: forty-one dogs with superficial corneal ulcers, and otherwise healthy, were enrolled in the study and randomly allocated into two groups. They all received standard therapy based on antimicrobial eye drops of ciprofloxaxin and use of an Elizabethan collar. With prior owner consent, blood samples were taken from group A, allowed clotting, and serum separated and stored in sterile containers for use topically on the affected eye. In addition to the standard therapy, patients received either 2 drops of autologous serum (group A) or 1 cc of the re-epitelializing ointment (group B) every hours 6 hours, and 10 minutes following the antimicrobial drops. Healing was monitored by measuring the wound size with calipers on days 3 and 7 of the follow-up, and a Mann-Whithey test was used to compare both groups (SAS, version 9.1). Results: no significant differences were observed between groups in the re-epithelization process. On day 3, the reduction of the disepithelialized area was 1.47 ± 1.42 and 1.26 ± 0.99 mm for groups A and B, respectively. By day 7, the average decrease was 0.94 ± 0.77 and 1.42 ± 1.21 mm for groups A and B, respectively. Conclusion: autologous serum was as effective as a commercial re-epithelializing ointment to treat uncomplicated corneal ulcer in dogs.